(untitled) (Research, Society and Development, 2023)
The importance of aesthetics has gained increasing prominence in planning dental treatments. Several factors have a direct influence on achieving facial balance and harmony. Autologous platelet aggregates have been widely used in various areas of medicine and dentistry, including regenerative procedures and facial harmonization. The objective of this study was to analyze the application of iPRF (Injectable Fibrin-Rich Plasma) in improving facial aesthetics. The methodology used to carry out this research consisted of a literature review, through the analysis of scientific data from books and articles.